PENGARUH KOMITE AUDIT TERHADAP PENGUNGKAPAN PENGENDALIAN INTERNAL - Fitriany Br Simbolon; Lenita Waty (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This research purpose is to examine the effect of the audit committee characteristic with audit committee expertise, genders in audit committee, and company age as the indicators and internal control research as the dependent variable. This research used data that obtained from the Indonesia Stock Exchange (IDX) from 2019 to 2020. For the sample, this research used 41 banking companies that registered on the IDX result from purposive sampling method. The multiple regressionis used in this research for the statistiacal technique. The final results of this research indicate that the knowledge of the audit committee and the gender in audit committee have a positive effect on internal control disclosure.